2001
DOI: 10.1136/bmj.323.7312.536
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of permanent childhood hearing impairment in the United Kingdom and implications for universal neonatal hearing screening: questionnaire based ascertainment study Commentary: Universal newborn hearing screening: implications for coordinating and developing services for deaf and hearing impaired children

Abstract: Objective To estimate the prevalence of confirmed permanent childhood hearing impairment and its profile across age and degree of impairment in the United Kingdom. Design Retrospective total ascertainment through sources in the health and education sectors by postal questionnaire. Setting Hospital based otology and audiology departments, community health clinics, education services for hearing impaired children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
250
1
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(275 citation statements)
references
References 23 publications
9
250
1
15
Order By: Relevance
“…Our results are in concordance with previous studies which have found that conductive hearing loss is more prevalent than sensorineural one among school children [8,18]. The prevalence of unilateral sensorineural hearing loss among school-children is reported to be 3%-5% [6,15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in concordance with previous studies which have found that conductive hearing loss is more prevalent than sensorineural one among school children [8,18]. The prevalence of unilateral sensorineural hearing loss among school-children is reported to be 3%-5% [6,15].…”
Section: Discussionsupporting
confidence: 83%
“…A large study including more than 6000 children aged 6-19 years reported that 14.9% of them had some kind of hearing impairment [15], a study among 6581 grade 1 and grade 5 children in Australia found that the prevalence of slight/moderate bilateral sensorineural hearing loss was 0.88% [16] whereas a UK study suggested that 2.05% of children aged 9-16 years had permanent hearing impairment [17]. In developed countries, the prevalence of hearing impairments among primary school children ranged from 8.8% in Iran [18], 15% in Malasyia [8] but 2.4% in Zimbabwe [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, virtually all previous studies have been conducted in localized populations so that their wider relevance is unclear. Although the contribution of mtDNA mutations to congenital (prelingual, early childhood onset) deafness is minor, 20,21 mitochondrial involvement in the much larger group of patients with postlingual hearing impairment, that is, with onset during childhood or early adulthood, 22,23 whether familial or sporadic, has not been studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hearing impairment is associated with a large range of consequences on the child's social, cognitive, emotional, and neuromotor development. [3][4][5] Previous research has concentrated on the impact of hearing impairment on language development and mental health.…”
mentioning
confidence: 99%